2016
DOI: 10.1007/s40261-016-0427-6
|View full text |Cite
|
Sign up to set email alerts
|

Teneligliptin, a Chemotype Prolyl-Thiazolidine-Based Novel Dipeptidyl Peptidase-4 Inhibitor with Insulin Sensitizing Properties

Abstract: These results indicate that: (i) teneligliptin ameliorates insulin sensitivity and non-HDL-C levels in subjects with high degrees of insulin resistance. This is not the case with sitagliptin, though similar glycemic efficacies were observed. (ii) glycemic efficacy of teneligliptin may be determined by the balance of its capacity in modulating insulin resistance and beta-cell function depending on the degrees of baseline insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Similarly, DPP-4 inhibitor, sitagliptin and teneligliptin study in type 1 DM patients showed decreased meal stimulated glucagon levels, still unlicensed for type 1 DM and requires large clinical trials to confirm its safety and efficacy for their use in clinical practice. 32 Alpha Cell Dysfunction in Type 2 DM Alpha-cells have a guardian type of role in the islet to maintain the body's capacity to produce insulin 33 and in health the α-and β-cells in the islet regulate each other reciprocally and systemic glucose levels are maintained within narrow range. But, the role of alpha cell in diabetes has been neglected for a long time despite suggested as "bihormonal" disease with an absolute or relative excess of glucagon, which causes higher rate of hepatic glucose production than utilisation favouring hyperglycaemia.…”
Section: Neural Regulationmentioning
confidence: 99%
“…Similarly, DPP-4 inhibitor, sitagliptin and teneligliptin study in type 1 DM patients showed decreased meal stimulated glucagon levels, still unlicensed for type 1 DM and requires large clinical trials to confirm its safety and efficacy for their use in clinical practice. 32 Alpha Cell Dysfunction in Type 2 DM Alpha-cells have a guardian type of role in the islet to maintain the body's capacity to produce insulin 33 and in health the α-and β-cells in the islet regulate each other reciprocally and systemic glucose levels are maintained within narrow range. But, the role of alpha cell in diabetes has been neglected for a long time despite suggested as "bihormonal" disease with an absolute or relative excess of glucagon, which causes higher rate of hepatic glucose production than utilisation favouring hyperglycaemia.…”
Section: Neural Regulationmentioning
confidence: 99%